Ex 3.3

Ex 3.3, 1
Important

Ex 3.3, 2 Important

Ex 3.3, 3 Important

Ex 3.3, 4

Ex 3.3, 5 (i) Important

Ex 3.3, 5 (ii)

Ex 3.3, 6 Important

Ex 3.3, 7

Ex 3.3, 8 Important

Ex 3.3, 9 Important

Ex 3.3, 10

Ex 3.3, 11 Important

Ex 3.3, 12 You are here

Ex 3.3, 13 Important

Ex 3.3, 14

Ex 3.3, 15

Ex 3.3, 16 Important

Ex 3.3, 17

Ex 3.3, 18 Important

Ex 3.3, 19

Ex 3.3, 20

Ex 3.3, 21 Important

Ex 3.3, 22 Important

Ex 3.3, 23 Important

Ex 3.3, 24

Ex 3.3, 25

Chapter 3 Class 11 Trigonometric Functions

Serial order wise

Last updated at April 8, 2024 by Teachoo

Ex 3.3, 12 Prove that sin2 6𝑥 – sin2 4𝑥 = sin2𝑥 sin10𝑥 Solving L.H.S. sin2 6x – sin2 4x = (sin 6x + sin 4x) (sin 6x – sin 4x) Lets calculate (sin 6x + sin 4x) and (sin 6x – sin 4x) separately sin 6x + sin 4x = 2 sin ((6x+4x)/2) cos ((6x−4x)/2) = 2sin (10𝑥/2) cos (2𝑥/2) = 2sin 5x cos x sin 6x – sin 4x = 2 cos ((6x+4x)/2) sin((6x−4x)/2) = 2 cos (10𝑥/2) sin (2𝑥/2) = 2 cos 5x sin x Hence sin2 6x – sin2 4x = (sin 6x + sin 4x) (sin 6x – sin 4x) = (2 sin 5x cos x) (2 cos 5x sin x) = (2 sin 5x cos 5x) . (2 sin x cos x) = (sin 10x) × (sin 2x) = R.H.S. Hence, L.H.S. = R.H.S. Hence proved